The 11th annual pillars of Lasallian educators excellence awards - Office of the Provost - De La Salle University, Manila (Animo Repository, 2023)
De La Salle University held the Annual Pillars of Lasallian Education Excellence Awards on January 25, 2023, Wednesday. There was a Thanksgiving Mass, at 12:00 noon, at the PGP Chapel. Afterward, the event began at exactly 2:30 p.m.